A Two-Year Longitudinal Assessment of Ophthalmologists’ Perceptions after Implementing an Electronic Health Record System - Ehrlich, Joshua R.; Michelotti, Monica; Blachley, Taylor S.; Zheng, Kai; Couper, Mick P.; Greenberg, Grant M.; Kileny, Sharon; Branford, Greta L.; Hanauer, David A.; Weizer, Jennifer S. (Applied Clinical Informatics, 2016)
Objectives To understand the attitudes and perceptions of ophthalmologists toward an electronic health record (EHR) system, before and after its clinical implementation.Methods Ophthalmologists at a single large academic ophthalmology department were surveyed longitudinally before and after implementation of a new EHR system. The survey measured ophthalmologists’ attitudes toward implementation of a new EHR. Questions focused on satisfaction, efficiency, and documentation. All attending physicians (between 56 and 61 at various time points) in the University of Michigan Department of Ophthalmology and Visual Sciences were surveyed. We plotted positive responses to survey questions and assessed whether perceptions followed a J-curve with an initial decrease followed by an increase surpassing pre-implementation levels.Results Survey responses were received from 32 (52%) ophthalmologists pre-implementation, and 28 (46%) at 3 months, 35 (57%) at 7 months, 40 (71%) at 13 months and 39 (67%) at 24 months post-implementation. After EHR implementation respondents were more likely to express concerns about their ability to create high-quality documentation (p<0.01) and the impact of an electronic health record on meaningful patient interaction (p<0.01). Physicians did not report a significant change in the amount of time spent documenting outside of regular clinical work hours (p=0.54) or on their clinic efficiency and workflow (p=0.97). There was no significant change in overall job satisfaction during the study period (p=0.69). We did not observe a J-curve for any of the survey responses analyzed.Conclusions As ophthalmology practices continue to transition to EHRs, adapting them to their specific culture and needs is important to maintain efficiency and user satisfaction. This study identifies areas of concern to ophthalmologists that may be addressed through education of physicians and customization of software as other practices move forward with EHR implementation.Citation: Ehrlich JR, Michelotti M, Blachley TS, Zheng K, Couper MP, Greenberg GM, Kileny S, Branford GL, Hanauer DA, Weizer JS. A two-year longitudinal assessment of ophthalmologists’ perceptions after implementing an electronic health record system.
Keywords: Ophthalmology; implementation and deployment; electronic health records and systems; testing and evaluation; clinical documentation and communications